Intrapersonal day-to-day travel variability and duration of household travel surveys: Moving beyond the one-day convention - Wei Li; Douglas Houston; Marlon G. Boarnet; Han Park (Journal of Transport and Land Use)
By analyzing seven-day travel logs from Los Angeles during 2011–2013, we contribute to the understanding of intrapersonal day-to-day travel variability (IDTV) in relation to socio-demographic and land-use characteristics and the implication of travel survey duration for travel parameter estimates. Our main sample included 2,395 person-days from 352 individual participants in 219 households. Our analytical methods included linear regressions and random sampling experiments.